22 Long term outcomes in children with functional neurological disorders; a retrospective, single centre case note and telephone audit. (17th August 2022) - Siafaka, Charoula; Shukla, Vanita; Hannon, Faith; Hameed, Biju; Majumdar, Anirban
Abstract : Aims: Patients presenting with physical symptoms for which no disease pathology can be found are common in medical practice. For most, symptoms are short lived; for others they may persist for months or years and can be extremely disabling. Previously the pendulum for the explanation of functional disorders swung strongly towards a psychiatric/psychological model. More recently a model in which both 'neurology and psychiatry', 'brain and mind' are equally important has formed, supported by the weight of evidence from biological and neuro-imaging studies. A successful management plan integrates various sub-specialities and therapies and provides a holistic, child and family-focused route to recovery and rehabilitation. Failure to integrate medical and therapy input may result in poor outcome and slower recovery. There exists remarkably little information about Functional Neurological Disorders (FND) in the paediatric population, especially regarding long-term outcomes. The aim of this project was to begin to address the gap in knowledge by determining and quantifying long term outcomes for paediatric patients diagnosed with FND in order to better understand the issues facing these children and young people. Methods: Patients were selected from a single centre and the personal case series of two Consultant Paediatric Neurologists. Diagnoses were reviewed retrospectively by interrogation of case notes and electronic records. In instances of uncertain diagnostic classification, a consensus was reached after a second review of each case. Demographic information was collected including gender and age at diagnosis, diagnostic subcategory at time of diagnosis, and information relating to progression and duration of symptoLongterm outcomes were determined with a telephone consultation using a structured questionnaire and were categorised into medical, social, psychological and educational/career domains. Results: A total of 60 patients were initially identified for inclusion (35% males and 65% females). Medical information was available for 51 of these patients. Telephone consultation through structured questionnaires was successful in 41 patients (80%), of which 23 (56%) were female. Only two patients described themselves as asymptomatic. 63% of patients described themselves as having multiple ongoing symptoms, with headaches and sensory symptoms the most common isolated ongoing sympto( table 1 ). Looking at longterm outcome domains ( table 2 ), there was no statistical significance between male and female patients regarding ongoing need for psychological support (p=0.923) or restriction on social life (p=0.677). There was a statistically significant difference in education completion (p=0.06) and career prospects (p=0.026) between genders, with males being more affected. Of those patients who were mono-symptomatic at presentation (n=22), 12 patients (54.5%) reported that their education, career and social life had not been affected. Conversely, for those patients who were poly-symptomatic at initial presentation (n=19), only 4 (21.1%) patients reported not being negatively affected in the long term. Conclusion: Whilst previous research has demonstrated implementation of a multidisciplinary treatment plan, including Physiotherapy and Psychology support, having positive impacts on short term outcome, this study revealed that in the longer term, these patients have ongoing morbidity, with only two patients describing themselves as asymptomatic at follow up. Our findings suggest that FND are more debilitating and disabling than recognised previously.